Hohenbergia alba and Hohenbergia sparsiflora, two striking new bromeliads from the Brazilian Atlantic Forest - Cavalcante, Brayan Paiva; Silva, Clécio Danilo Dias Da; Souza, Everton Hilo De; Versieux, Leonardo M.; Martinelli, Adriana Pinheiro (Phytotaxa, 2024)
We present two new species, Hohenbergia alba and H. sparsiflora, endemic to the Brazilian Atlantic Forest in the southern region of the state of Bahia. These species were identified as understory epiphytes in forest fragments near highways. These newly described species are morphologically similar to the “giant Hohenbergia species group”, characterized by their significantly larger size compared to species found in the highlands and dryer environments. Notable unique features include the compact rosette and a 3-4-branched inflorescence with white-colored petals for H. alba and sparsely-flowered spikes for H. sparsiflora, a feature not yet reported for the genus. Additionally, we provide illustrations, and a comparative table of morphological data of these species and related taxa, as well as information on the conservation status and phenology.